AIESEC connects youths to business leaders - Campus, Plus (Campus Plus, 2013)
800 students and fresh graduates had the rare chance to connect with key corporate leaders from Multimedia Super Corridor (MSC), Ernst & Young, Microsoft, and Accenture at the recently concluded Malaysian Youth to Business Forum (Y2B). Organised by AIESEC in Malaysia at Taylor's University, the forum themed 'How To Build Malaysia's Youth To Be A Future Competitive Business Leader Globally' was divided into three main streams, which were Entrepreneurship, Innovation and Corporate Social Responsibility.